3,4-methylenedioxymethamphetamine (MDMA) assisted therapy for the treatment of social anxiety in autistic adults (Research, Society and Development, 2024)
Autism spectrum disorder is a neurodevelopmental condition that causes deficits in an individual's interpersonal interaction and communication, which can lead to the development of social anxiety. The lack of an effective pharmacological treatment with reduced side effects has attracted researchers' attention to treatment with alternative approaches. 3,4-methylenedioxymethamphetamine (MDMA) is a synthesized active compound, found in Ecstasy, capable of producing a great sensation of affection and pro-social intentions, increasing the release of serotonin, dopamine and oxytocin, facilitating the process of social interaction. The objective of this article was to inform, through a bibliographic survey, about the history of clinical research with psychedelics, especially MDMA, its influence on the treatment of social anxiety in adults with autism spectrum disorder and to encourage future studies with these substances. A bibliographical review was carried out from 1986 to 2023 through Pubmed and SciELO. The historical context and pharmacology of MDMA were described, as well as its importance and interaction in the social anxiety of adults with autism. The mechanism of action was reported in order to justify the therapeutic possibilities associated with the use of MDMA. As a result, data on significant improvements in the symptoms of social anxiety in the study subjects were obtained, and its prescription was authorized in Australia for the treatment of Post-Traumatic Stress Disorder, becoming very promising in the search for an effective medication for the Treatment of social anxiety in people with autism spectrum disorder.